2019
DOI: 10.1177/0956797618815488
|View full text |Cite
|
Sign up to set email alerts
|

A Tight Spot: How Personality Moderates the Impact of Social Norms on Sojourner Adaptation

Abstract: How do you navigate the norms of your new culture when living abroad? Taking an interactionist perspective, we examined how contextual factors and personality traits jointly affect sojourners’ adaptation to the host-country culture. We hypothesized that tightness (strong, rigidly imposed norms) of the host culture would be associated with lower levels of adaptation and that tightness of the home culture would be associated with higher levels of adaptation. Further, we proposed that the impact of tightness shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 37 publications
(42 reference statements)
1
41
1
Order By: Relevance
“…Regarding context factors, positive, integration-promoting effects should be facilitated by communal, PSYCHOLOGY OF REFUGEE INTEGRATION 25 collectivistic (Abele & Wojciszke, 2007), and, more specifically, multicultural orientations of the hosting society (Ward et al, 2018). Integration-impeding effects should be more likely when the environment in the receiving society provides more (vs. less) salient cues to rejection and aggression, and when the receiving society culture is generally tight (vs. loose) (Geeraert, Li, Ward, Gelfand, & Demes, 2019).…”
Section: Perceptions and Memories Of Suffering And Violencementioning
confidence: 99%
“…Regarding context factors, positive, integration-promoting effects should be facilitated by communal, PSYCHOLOGY OF REFUGEE INTEGRATION 25 collectivistic (Abele & Wojciszke, 2007), and, more specifically, multicultural orientations of the hosting society (Ward et al, 2018). Integration-impeding effects should be more likely when the environment in the receiving society provides more (vs. less) salient cues to rejection and aggression, and when the receiving society culture is generally tight (vs. loose) (Geeraert, Li, Ward, Gelfand, & Demes, 2019).…”
Section: Perceptions and Memories Of Suffering And Violencementioning
confidence: 99%
“…Many researchers have become interested in what individual and groups factors impact on sojourner adjustment using person-environment fit models. Thus Valenzuela and Rogers (2018) noted how the Big Five personality traits related to different acculturation strategies while Geeraert et al (2019) in a longitudinal study identified Agreeable and Honesty-Humility as important traits in the process of sojourner adjustment.…”
Section: Explaining Culture Shockmentioning
confidence: 99%
“…Psychology, 10, 1832-1855. https://doi.org/10. 4236/psych.2019.1013119 Psychology sojourners (Geereaet, Li, Ward, Gelfand, & Demes, 2019) and expatriates (Valenzuela & Rogers, 2018) as well as the often ignored shock of being visited: namely a host person coming into contact with travelers to his or her home (McGhee, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…climate) and social environment (e.g. cultural values, social norms or thinking) can be extremely challenging for newcomers [ 18 ]. For instance, scholars have carried out some investigations on how these differences in physical and social environment directly impact international sojourners [ 19 ].…”
Section: Introductionmentioning
confidence: 99%